The predictive power of pollination syndromes: Passerine pollination in heterantherous Meriania macrophylla (Benth.) Triana (Melastomataceae) - Valverde Espinoza, José Miguel (2021)
The cloud forest species Meriania macrophylla (Benth.) Triana has pseudocampanu- late flowers with bulbous stamen appendages, typical for the passerine pollination syndrome found in the Melastomataceae tribe Merianieae. The species is further characterized by strong stamen dimorphism (heteranthery), a condition otherwise associated with pollen-rewarding bee-pollinated species (both in Melastomataceae and beyond). In passerine-pollinated Merianieae, however, flowers usually only show weak stamen dimorphism. Here, we conducted field and laboratory investigations to determine the pollinators of M. macrophylla and assess the potential role of strong heteranthery in this species. Our field observations in Costa Rica confirmed syn- drome predictions and indeed proved pollination by passerine birds in M. macrophylla. The large bulbous set of stamens functions as a food-body reward to the pollinating birds, and as trigger for pollen release (bellows mechanism) as typical for the pas- serine syndrome in Merianieae. In contrast to other passerine-pollinated Merianieae, the second set of stamens has seemingly lost its rewarding and pollination function, however. Our results demonstrate the utility of the pollination syndrome concept even in light of potentially misleading traits such as strong heteranthery.